In Silico chloroplast SSRs mining of Olea species - ERTUGRUL FILIZ; IBRAHIM KOC (Society for Indonesian Biodiversity, 2012)
Filiz E, Koc E. 2012. In Silico chloroplast SSRs mining of Olea species. Biodiversitas 13: 114-117. Simple sequence repeat (SSR) markers are highly informative and have been widely applied as molecular markers in genetic studies. The purpose of present study is to analyze the occurrence and distribution of chloroplast SSRs in genic and intergenic regions from Olea species viz., Olea europaea, Olea europaea subsp. cuspidate, Olea europaea subsp. europaea, Olea europaea subsp. maroccana, Olea woodiana subsp. woodiana by using bioinformatics tools. We identified 1149 chloroplast SSRs (cpSSRs) in all genome and a total of 340 (29.6%) was located in genic regions. It was observed that the most abundant repeat types were found mononucleotide SSR (66.7 %) followed by trinucleotide SSR (28.3 %), dinucleotide (2.7%), tetranucleotide (1.5%) and pentanucleotide (0.8%). cpSSRs located in genic regions were identified only mono- and trinucleotide motifs, the most abundant of which was trinucleotide (16.2%) followed by mononucleotide (14.3%). All types of repeat motif (mono-, di-, tri-, tetra- and pentanucleotide) were detected except hexanucleotide motifs. According to SSRs analysis, the most abundant observed motifs were identified for mono-, di-, tri-, tetra- and pentanucleotide cpSSRs A/T, AT/TA, AAG/CTT, AAAG/AGTTT, and AATCC/ATTGG respectively. This study results provided scientific base for phylogenetics, evolutionary genetics and diversity studies on different Olea species in future.